2015
DOI: 10.1016/j.joca.2015.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhanced imaging of human meniscus using cone beam CT

Abstract: The cross-sectional distribution of CA was consistent with that reported in a previous μCT study on bovine meniscus. The time required to reach diffusion equilibrium was found impractical for clinical applications. However, based on the present results, shorter delay between injection and imaging (e.g., 40 min) could be feasible in clinical diagnostics of meniscal pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 48 publications
2
17
1
Order By: Relevance
“…CT measures the retention of X‐rays when they go through targets. The capacity of CT to recognize tissues depends on the way that diverse tissues give unmistakable degrees of X‐ray attenuation, where the weakening coefficient depends upon the nuclear number and electron thickness of the tissues . Bone, fat, air, and water have different absorption differences and this creates high complexity images of anatomical structures.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…CT measures the retention of X‐rays when they go through targets. The capacity of CT to recognize tissues depends on the way that diverse tissues give unmistakable degrees of X‐ray attenuation, where the weakening coefficient depends upon the nuclear number and electron thickness of the tissues . Bone, fat, air, and water have different absorption differences and this creates high complexity images of anatomical structures.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Due to the electrostatic interaction between the GAGs’ negative fixed charge density and the anionic charge of ioxaglate, color maps are expected to depict an inverse representation of the negatively charged GAGs in the meniscus, as has been previously reported for bovine and human meniscus samples. This inverse relationship is best depicted at concentrations greater than or equal to 80 mgI/ml, as the outer subregion exhibited greater CECT attenuation than the inner and middle subregions (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…An alternative to MRI, contrast‐enhanced CT (CECT) enables ex vivo measurement of both bovine and human meniscal GAG content and distribution. Using the anionic contrast agent ioxaglate, the reported associations between the mean CECT attenuation and the GAG contents of both bovine and human meniscus samples were significant but weak to moderate in association strength—bovine, R 2 = 0.51 ( p < 0.05) and human, R 2 ≤ 0.49 ( p < 0.05)—indicating that there is a need for a more sensitive technique for determining meniscal GAG content non‐destructively . Recently, a new cationic CT contrast agent CA4+ is described for imaging articular cartilage that is also sensitive to bovine meniscal GAG content and distribution, but there are no reports of its performance in human meniscal tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The contrast agent partition in intact cartilage (International Cartilage Repair Society, ICRS, grade 0) was lower than that of cartilage surrounding the ICRS grade IeIV lesions 8 . Another study used contrast enhanced CBCT to image contrast agent diffusion in isolated human menisci and found that shorter delay between injection and imaging (e.g., 40 min) could be feasible in clinical diagnostics of meniscal pathologies 9 . These findings suggest that CBCT enables not only quantitative analyses of articular cartilage, but also subchondral bone volumetric BMD.…”
Section: New Lessons From Ctmentioning
confidence: 99%